Method for stabilizing ZnOHF protective layer in zinc sulfate and application of method in aqueous zinc ion battery
By stabilizing the ZnOHF protective layer and regulating the electrolyte components in the aqueous zinc ion battery, the dendrite and side reaction problems of the negative electrode of the zinc ion battery are solved, and the cycle stability and deposition and dissolution reversibility of the battery are significantly improved.
Patent Information
- Application Number
- CN202311184292.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-13
AI Technical Summary
The negative electrode of the aqueous zinc ion battery faces problems such as dendrites and side reactions, resulting in short circuits, reduced cycle life and affected safety performance.
By stabilizing the ZnOHF protective layer in zinc sulfate and synergistically adjusting the electrolyte component, the deposition and solubility of zinc negative electrode is improved, and the occurrence of dendrites and side reactions is inhibited.
It realizes efficient protection of zinc negative electrode, significantly improves the cycle stability and deposition and dissolution reversibility of zinc ion batteries, and extends the cycle life of the battery.
Smart Images

Figure HDA0004448286310000011 
Figure HDA0004448286310000021 
Figure HDA0004448286310000031
Abstract
Description
Technical Field
[0001] The invention relates to a method for stabilizing a ZnOHF protective layer in zinc sulfate and application thereof in an aqueous zinc ion battery, namely a negative electrode protection method for improving the reversibility of zinc deposition and dissolution in a zinc ion battery, and belongs to the field of electrochemistry. Background Art
[0003] Zinc metal reserves are abundant in my country (ranking first in the world), and it has the advantages of low cost, non-toxicity and high theoretical capacity (5851mAh / mL; 820mAh / g). Its relatively low redox potential (-0.76V vs SHE) allows zinc ion batteries to directly use aqueous electrolytes. The ionic conductivity of aqueous electrolytes is about two orders of magnitude higher than that of organic electrolytes (~1000mS cm -1 vs~1-10mS cm -1 ), so aqueous zinc-ion batteries can be charged and discharged quickly. In addition, thanks to the relatively stable chemical and physical properties of zinc metal, aqueous zinc-based batteries have no risk of explosion or fire. Their high safety makes them have great potential in portable devices, electric vehicles and large-scale energy storage.
[0004] However, the negative electrode of aqueous zinc-ion batteries currently faces key problems such as dendrites and side reactions, which can lead to battery short-circuit failure and reduced cycle life. Zinc dendrites can easily pierce the diaphragm and cause battery short circuits. At the same time, side reactions not only reduce the utilization rate of zinc and the overall coulombic efficiency of the battery, but also the hydrogen evolution reaction will affect the safety and electrochemical performance of the battery. Therefore, effectively inhibiting the occurrence of zinc dendrites and side reactions is a difficult problem that must be solved in the development of zinc-ion batteries. Summary of the invention
[0005] The purpose of the present invention is to avoid zinc dendrites and side reactions, thereby improving the cycle stability of the negative electrode of a zinc ion battery. The present invention provides a method for stabilizing a ZnOHF protective layer in zinc sulfate, that is, a zinc negative electrode protection method that improves the reversibility of zinc negative electrode deposition and dissolution in a zinc ion battery through the synergistic effect of the ZnOHF protective layer and the regulation of electrolyte components. That is, by adjusting the components and concentrations of the electrolyte in the battery system, the ZnOHF protective layer, which was originally unstable in the zinc sulfate electrolyte, is stably present, and the zinc deposition behavior is guided at the electrode and electrolyte interface on the zinc negative electrode side of the zinc ion battery, while effectively inhibiting side reactions such as hydrogen evolution and water corrosion, thereby showing excellent zinc deposition and dissolution reversibility. The battery cycle performance results show that the synergistic strategy inhibits the occurrence of zinc dendrites and side reactions, and has efficient and reversible deposition and dissolution performance; the method is simple and low cost.
[0006] A method for protecting the zinc negative electrode in a stable zinc ion battery is achieved by coordinating the electrolyte regulation and the ZnOHF protective layer. The method is characterized in that the ZnOHF that would otherwise be converted into a byproduct in ZnSO4 can be stabilized, and only one foreign ion is introduced. First, a protective layer with adjustable morphology and thickness is prepared on the surface of a zinc substrate. The method is characterized in that a ZnOHF protective layer (abbreviated as ZnOHF@Zn) with adjustable morphology and thickness can be prepared on a zinc substrate by electrolyzing the traditional two electrodes at a constant voltage for a certain period of time. The solvent of the zinc ion battery electrolyte is water, and the solutes are zinc fluoride (ZnF2) and zinc sulfate (ZnSO4).
[0007] The present invention provides a neutral zinc ion battery protection method, characterized in that: the negative electrode is a zinc substrate with a ZnOHF protective layer plated on the surface; the solvent of the electrolyte is water, and the solutes are zinc fluoride (ZnF2) and zinc sulfate (ZnSO4). The optimization of the ZnOHF protective layer and the electrolyte components can synergistically improve the reversibility of zinc negative electrode deposition and dissolution.
[0008] Furthermore, in the above technical solution, a conventional two-electrode device is used to prepare the ZnOHF protective layer, wherein the working electrode is a zinc substrate, the counter electrode is an inert electrode, the electrolyte solvent is water, and the solute is NH4F. The device is electrolyzed at a constant voltage for a certain period of time; that is, a ZnOHF protective layer is formed on the surface of the zinc substrate.
[0009] Furthermore, in the above technical solution, in preparing the protective layer, the electrolyte concentration is 1-2M.
[0010] Furthermore, in the above technical solution, when preparing the protective layer, the constant voltage is 6 to 15V.
[0011] Furthermore, in the above technical solution, in the preparation of the protective layer, the electrolysis time is 2 to 120 seconds.
[0012] Furthermore, in the above technical solution, in the preparation of the protective layer, the optimal electrolyte concentration is 2M, the optimal constant voltage is 15V, and the optimal electrolysis time is 2s.
[0013] Furthermore, in the above technical solution, the electrolyte is prepared by first preparing a 1-2M ZnSO4 solution, wherein the solvent is water and the solute is ZnSO4, then weighing a certain amount of zinc fluoride powder, then adding a certain volume of a certain concentration of ZnSO4 solution, and magnetically stirring for 1 day. The optimal electrolyte preparation method is to first prepare a 2M ZnSO4 solution, wherein the solvent is water and the solute is ZnSO4, then weighing 0.0827g of zinc fluoride powder, then adding 10mL of 2M ZnSO4, and magnetically stirring for 1 day.
[0014] Furthermore, in the above technical solution, the zinc substrate is zinc sheet, zinc foil, zinc powder, zinc mesh, porous zinc or zinc alloy.
[0015] Furthermore, in the above technical solution, the counter electrode in the preparation of the ZnOHF protective layer is a carbon paper or a platinum electrode.
[0016] Furthermore, in the above technical solution, the solvent in the zinc ion battery electrolyte is water, and the solutes are zinc fluoride (ZnF2) and zinc sulfate (ZnSO4); the concentrations are 0.07-0.09M and 1-2M, respectively. The optimal zinc fluoride concentration is 0.08M, and the optimal zinc sulfate (ZnSO4) concentration is 2M.
[0017] The application of the ZnOHF protective layer and fluorine-containing electrolyte prepared by the above method in zinc ion batteries shows excellent reversibility of zinc deposition and dissolution when used as negative electrode protection of zinc ion batteries. The process is as follows:
[0018] Place the zinc sheet coated with ZnOHF protective layer in the center of the negative electrode shell, then place the GF separator on it and wet the separator with the regulated electrolyte, then put the zinc sheet coated with ZnOHF protective layer, gasket, spring in turn, and finally buckle the positive electrode shell and use the button battery packaging machine to complete the packaging of the zinc negative electrode symmetrical battery. The packaged battery is connected to the electrochemical charge and discharge instrument, and the specified current density (0.1~20mA / cm 2 ) was used to conduct a cyclic stability test.
[0019] Beneficial results:
[0020] The present invention adopts ZnOHF protective layer and regulated electrolyte to synergistically increase the cycle stability of zinc negative electrode during zinc cyclic deposition. The comparison of battery thickness after cycling shows that this strategy effectively inhibits hydrogen evolution reaction ( Figure 6 ), XRD test results show that the zinc sheet after recycling inhibits the formation of by-products ( Figure 7 The zinc symmetric battery exhibits excellent zinc deposition and dissolution reversibility at 0.5 mA / cm 2 At a current density of , the cycle life can reach 3100h ( Figure 5 ).
[0021] The method provided by the invention has short time consumption, simple steps, low cost and good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the XRD diagram of the ZnOHF protective layer in Example 1-3.
[0023] Figure 2 This is the SEM image of the ZnOHF protective layer in Example 1-3.
[0024] Figure 3 XRD and SEM images of the ZnOHF protective layer after immersion in 2M ZnSO4 for 2h.
[0025] Figure 4 XRD and SEM images of the ZnOHF protective layer after being immersed in the regulated electrolyte for 1 day.
[0026] Figure 5 The voltage-time curves of the battery cycle stability test in Examples 1-3 and Comparative Examples 1-3.
[0027] Figure 6 The battery thickness after cycling in Example 1 and Comparative Example 1 was measured.
[0028] Figure 7 2 is the XRD diagram of the battery after cycling in Example 1-2 and Comparative Example 1. DETAILED DESCRIPTION
[0029] The following examples will further illustrate the present invention, but are not intended to limit the invention.
[0030] Example 1
[0031] Preparation of ZnOHF protective layer: The preparation method is to use a traditional two-electrode device, in which the working electrode is a zinc sheet, the counter electrode is a platinum electrode, the electrolyte solvent is water, and the solute is NH4F, that is, a 2M NH4F aqueous solution is prepared, and the device is electrolyzed at a constant voltage of 15V for 2s. The X-ray diffraction (XRD) spectrum of the material is shown in Figure 1 , the SEM image of the microscopic surface morphology is shown in Figure 2 ;
[0032] Preparation of zinc ion battery electrolyte: weigh 0.0827 g zinc fluoride powder and dissolve it in 10 mL 2M ZnSO4, stir magnetically for 1 day, and prepare 0.08 M ZnF2-ZnSO4 mixed electrolyte.
[0033] The prepared ZnOHF protective layer zinc sheet and the electrolyte were used to assemble a zinc ion symmetrical battery, that is, the zinc sheet coated with the ZnOHF protective layer was placed in the center of the negative electrode shell, the GF separator was placed on it, and the separator was moistened with the regulated electrolyte, and then the zinc sheet coated with the ZnOHF protective layer, the gasket, and the spring were placed in sequence, and finally the positive electrode shell was buckled and the zinc negative electrode symmetrical battery was packaged using a button battery packaging machine. At 0.5 mA / cm 2 At a current density of , the voltage-time curve of the symmetrical battery cycle stability test is shown in Figure 5 ; Battery thickness measurement after cycling see Figure 6 ; The X-ray diffraction (XRD) spectrum results after battery cycling are shown in Figure 7 .
[0034] Example 2
[0035] Preparation of ZnOHF protective layer: The preparation method is to use a traditional two-electrode device, in which the working electrode is a zinc sheet, the counter electrode is a platinum electrode, the electrolyte solvent is water, and the solute is NH4F, that is, a 2M NH4F aqueous solution is prepared, and the device is electrolyzed at a constant voltage of 10V for 10s. The X-ray diffraction (XRD) spectrum of the material is shown in Figure 1 , the SEM image of the microscopic surface morphology is shown in Figure 2 ;
[0036] Preparation of zinc ion battery electrolyte: weigh 0.0827 g zinc fluoride powder and dissolve it in 10 mL 2M ZnSO4, stir magnetically for 1 day, and prepare 0.08 M ZnF2-ZnSO4 mixed electrolyte.
[0037] The prepared ZnOHF protective layer zinc sheet and the electrolyte were used to assemble a zinc ion symmetrical battery, that is, the zinc sheet coated with the ZnOHF protective layer was placed in the center of the negative electrode shell, the GF separator was placed on it, and the separator was moistened with the regulated electrolyte, and then the zinc sheet coated with the ZnOHF protective layer, the gasket, and the spring were placed in sequence, and finally the positive electrode shell was buckled and the zinc negative electrode symmetrical battery was packaged using a button battery packaging machine. At 1mA / cm 2 At a current density of , the voltage-time curve of the symmetrical battery cycle stability test is shown in Figure 5 ; The X-ray diffraction (XRD) spectrum results after battery cycling are shown in Figure 7 .
[0038] Example 3
[0039] Preparation of ZnOHF protective layer: The preparation method is to use a traditional two-electrode device, in which the working electrode is a zinc sheet, the counter electrode is a platinum electrode, the electrolyte solvent is water, and the solute is NH4F, that is, a 2M NH4F aqueous solution is prepared, and the device is electrolyzed at a constant voltage of 6V for 10s. The X-ray diffraction (XRD) spectrum of the material is shown in Figure 1 , the SEM image of the microscopic surface morphology is shown in Figure 2 ;
[0040] Preparation of zinc ion battery electrolyte: weigh 0.0827 g zinc fluoride powder and dissolve it in 10 mL 2M ZnSO4, stir magnetically for 1 day, and prepare 0.08 M ZnF2-ZnSO4 mixed electrolyte.
[0041] The prepared ZnOHF protective layer zinc sheet and the electrolyte were used to assemble a zinc ion symmetrical battery, that is, the zinc sheet coated with the ZnOHF protective layer was placed in the center of the negative electrode shell, the GF separator was placed on it, and the separator was moistened with the regulated electrolyte, and then the zinc sheet coated with the ZnOHF protective layer, the gasket, and the spring were placed in sequence, and finally the positive electrode shell was buckled and the zinc negative electrode symmetrical battery was packaged using a button battery packaging machine. At 10mA / cm 2At a current density of , the voltage-time curve of the symmetrical battery cycle stability test is shown in Figure 5 .
[0042] Example 4
[0043] Preparation of ZnOHF protective layer: The preparation method is to use a conventional two-electrode device, wherein the working electrode is a zinc sheet, the counter electrode is a carbon paper, the electrolyte solvent is water, and the solute is NH4F, that is, a 1M NH4F aqueous solution is prepared, and the device is electrolyzed at a constant voltage of 15V for 2s;
[0044] Preparation of zinc ion battery electrolyte: weigh 0.0827 g zinc fluoride powder and dissolve it in 10 mL 2M ZnSO4, stir magnetically for 1 day, and prepare 0.08 M ZnF2-ZnSO4 mixed electrolyte.
[0045] A zinc ion symmetrical battery is assembled using the prepared ZnOHF protective layer zinc sheet and the electrolyte, that is, the zinc sheet coated with the ZnOHF protective layer is placed in the center of the negative electrode shell, a GF diaphragm is placed thereon, the diaphragm is moistened with the regulated electrolyte, and then the zinc sheet coated with the ZnOHF protective layer, the gasket, and the spring are placed in sequence, and finally the positive electrode shell is buckled and the zinc negative electrode symmetrical battery is packaged using a button battery packaging machine.
[0046] Example 5
[0047] Preparation of ZnOHF protective layer: The preparation method is to use a conventional two-electrode device, wherein the working electrode is a zinc sheet, the counter electrode is a platinum electrode, the electrolyte solvent is water, and the solute is NH4F, that is, a 1M NH4F aqueous solution is prepared, and the device is electrolyzed at a constant voltage of 10V for 2s;
[0048] Preparation of zinc ion battery electrolyte: weigh 0.0827 g zinc fluoride powder and dissolve it in 10 mL 2M ZnSO4, stir magnetically for 1 day, and prepare 0.08 M ZnF2-ZnSO4 mixed electrolyte.
[0049] A zinc ion symmetrical battery is assembled using the prepared ZnOHF protective layer zinc sheet and the electrolyte, that is, the zinc sheet coated with the ZnOHF protective layer is placed in the center of the negative electrode shell, a GF diaphragm is placed thereon, the diaphragm is moistened with the regulated electrolyte, and then the zinc sheet coated with the ZnOHF protective layer, the gasket, and the spring are placed in sequence, and finally the positive electrode shell is buckled and the zinc negative electrode symmetrical battery is packaged using a button battery packaging machine.
[0050] Comparative Example 1
[0051] A zinc ion symmetrical battery was assembled using a commercial zinc sheet and a 2M ZnSO4 electrolyte, wherein the solvent of the electrolyte was water and the solute was ZnSO4. The commercial zinc sheet was placed in the center of the negative electrode shell, a GF separator was placed on it, and the separator was moistened with a 2M ZnSO4 electrolyte. Then, the commercial zinc sheet, gasket, and spring were placed in sequence. Finally, the positive electrode shell was buckled and the zinc negative electrode symmetrical battery was packaged using a button battery packaging machine. At 0.5 mA / cm 2 At a current density of , the voltage-time curve of the symmetrical battery cycle stability test is shown in Figure 5 ; Battery thickness measurement after cycling see Figure 6 ; The X-ray diffraction (XRD) spectrum results after battery cycling are shown in Figure 7 .
[0052] Comparative Example 2
[0053] Preparation of ZnOHF protective layer: The preparation method is to use a traditional two-electrode device, in which the working electrode is a zinc sheet, the counter electrode is a platinum electrode, the electrolyte solvent is water, and the solute is NH4F, that is, a 2M NH4F aqueous solution is prepared, and the device is electrolyzed at a constant voltage of 15V for 2s. The X-ray diffraction (XRD) spectrum of the material is shown in Figure 1 (Same as Example 1), SEM image of microscopic surface morphology is shown in Figure 2 (Same as Example 1);
[0054] The zinc ion symmetric battery was assembled using the prepared ZnOHF protective layer zinc sheet and 2M ZnSO4 electrolyte, wherein the solvent of the electrolyte was water and the solute was ZnSO4, that is, the zinc sheet coated with the ZnOHF protective layer was placed in the center of the negative electrode shell, the GF diaphragm was placed on it, and the diaphragm was wetted with 2M ZnSO4 electrolyte, and then the zinc sheet coated with the ZnOHF protective layer, the gasket, and the spring were placed in sequence, and finally the positive electrode shell was buckled and the zinc negative electrode symmetric battery was packaged using a button battery packaging machine. At 0.5mA / cm 2 At a current density of , the voltage-time curve of the symmetrical battery cycle stability test is shown in Figure 5 .
[0055] Comparative Example 3
[0056] Preparation of zinc ion battery electrolyte: weigh 0.0827 g zinc fluoride powder and dissolve it in 10 mL 2M ZnSO4, stir magnetically for 1 day, and prepare 0.08 M ZnF2-ZnSO4 mixed electrolyte.
[0057] The zinc ion symmetrical battery was assembled using the commercial zinc sheet and the electrolyte, that is, the commercial zinc sheet was placed in the center of the negative electrode shell, the GF separator was placed on it, and the separator was moistened with the regulated electrolyte, and then the commercial zinc sheet, gasket, and spring were placed in sequence, and finally the positive electrode shell was buckled and the zinc negative electrode symmetrical battery was packaged using a button battery packaging machine.2 At a current density of , the voltage-time curve of the symmetrical battery cycle stability test is shown in Figure 5 .
Claims
1. A neutral zinc ion battery, characterized in that: The negative electrode is a zinc substrate with a ZnOHF protective layer on the surface; the solvent of the electrolyte is water, and the solute is zinc fluoride (ZnF2) and zinc sulfate (ZnSO4).
2. A neutral zinc ion battery according to claim 1, characterized in that: Preparation of a zinc substrate coated with a ZnOHF protective layer on its surface: Use a two-electrode device, in which the working electrode is the zinc substrate, the counter electrode is an inert electrode, the electrolyte solvent is water, and the solute is NH4F, and electrolyze the device at a constant voltage for a certain period of time.
3. The neutral zinc ion battery according to claim 2, characterized in that: During the preparation of the protective layer, the electrolyte concentration is 1-2M.
4. The neutral zinc ion battery according to claim 2, characterized in that: During the preparation of the protective layer, the constant voltage is 6 to 15V.
5. The neutral zinc ion battery according to claim 2, characterized in that: During the preparation of the protective layer, the electrolysis time is 2 to 120 seconds.
6. The neutral zinc ion battery according to claim 2, characterized in that: During the preparation of the protective layer, the optimal electrolyte concentration was 2M, the optimal constant voltage was 15V, and the optimal electrolysis time was 2s.
7. The neutral zinc ion battery according to claim 1, characterized in that: The electrolyte preparation method is to first prepare a 1-2M ZnSO4 solution, wherein the solvent is water and the solute is ZnSO4, then weigh a certain amount of zinc fluoride powder, and then add a certain volume of a certain concentration of ZnSO4 solution, and stir magnetically for 1 day.
8. The neutral zinc ion battery according to claim 4, characterized in that: The zinc substrate is zinc sheet, zinc foil, zinc powder, zinc mesh, porous zinc or zinc alloy.
9. The neutral zinc ion battery according to any one of claims 2 to 6, characterized in that: In the preparation of ZnOHF protective layer, the counter electrode is carbon paper or platinum electrode.
10. The neutral zinc ion battery according to claim 1, characterized in that: The solvent in the neutral zinc ion battery electrolyte is water, and the solutes are zinc fluoride (ZnF2) and zinc sulfate (ZnSO4); the concentrations are 0.07-0.09M and 1-2M respectively.
Citation Information
Patent Citations
Low-cost aqueous zinc ion battery electrolyte as well as preparation method and application thereof
CN112652825A
Mixed aqueous zinc ion battery electrolyte with stable pH value and application
CN114865110A
Electrolyte for high-temperature safe aqueous zinc ion secondary battery, and preparation method and application thereof
CN115332646A
Zinc battery, electrode and manufacturing method therefor, and laminated film
JP2019185863A
Electrolyte solution for zinc battery and zinc battery
JP2020087554A